Expected health benefits from mitigation of emissions from major anthropogenic PM2.5 sources in India: Statistics at state level. (November 2018) - Upadhyay, Abhishek; Dey, Sagnik; Chowdhury, Sourangsu; Goyal, Pramila
Abstract: Exposure to fine particulate matter (PM2.5 ) is one of the leading risk factors for the mortality and morbidity burden in India. Health benefit expected from mitigation of emissions from individual sectors is the key policy information to address this issue. Here we quantify the relative shares of four major year-round anthropogenic sources to ambient PM2.5 in India using a chemical transport model and estimate premature deaths that could have been avoided due to complete mitigation of emissions from these sources at state level. Population-weighted all-India averaged (±1σ) annual ambient PM2.5 exposures due to residential, transport, industrial and energy sectors in 2010 are estimated to be 26.2 ± 12.5, 3.8 ± 4.3, 5.5 ± 2.7 and 2.2 ± 2.3 μg m −3, respectively. Complete mitigation of emissions from the transport, industrial and energy sectors combined would avoid 92, 380 (95% uncertainty interval (UI), 40, 918–140, 741) premature deaths annually, primarily at the urban hotspots. For the residential sector, this would result in avoiding 378, 295 (95% UI, 175, 002–575, 293) premature deaths due to a reduction in ambient PM2.5 exposure in addition to the benefit of avoiding all premature deaths from household exposure. Bihar and Goa are expected to have the largest (289) and smallest (48) premature mortality burden per 100, 000 population due to anthropogenic PM2.5 exposure. From policy perspective, controlling residential sources should be prioritized in view of the effectiveness of implementing mitigation measures and the expected larger health benefit at a regional scale. However, additional mitigation measures are advised at the urban hotspots to curb emissions from the other sectors to get maximum possible health benefit. Graphical abstract: Normalized frequency distribution of relative contributions of energy (Ene), industrial (Ind), transportation (Trans) and residential (Res) sources to annual ambient anthropogenic PM2.5 exposure over India. Note that the seasonal sources such as agricultural burning is not considered in the simulation. Frequency is computed based on number of model grid cells. Image Highlights: Contributions of four major anthropogenic sectors to ambient PM2.5 in India examined. Statistics at state level are provided. Source-apportioned burden (in terms of premature deaths) is estimated. Complete mitigation of transport, industrial and energy sectoral emission would save 92, 380 premature deaths. Complete mitigation of residential sector emission would save 378, 295 lives.